2010
DOI: 10.1111/j.1570-7458.2010.00997.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary yeasts on Drosophila melanogaster life‐history traits

Abstract: An organism's fitness is highly dependent on resource quality. The diet of saprobiotic organisms often comprises a variety of microorganisms. Saprophagous Drosophila melanogaster Meigen (Diptera: Drosophilidae) is known to feed on various yeast species, both as larva and adult. The yeasts encountered by the insects may differ in composition and quality, and thus in their influence on larval and adult performance. Our study explores life-history consequences of larval diet on selected larval and adult traits, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
151
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(170 citation statements)
references
References 44 publications
7
151
3
Order By: Relevance
“…Finally, since bacteria and fungi are recognized and cleared by semi-independent innate immunity pathways (42), a more nuanced control of the two symbiont groups is also possible. As both bacteria and yeasts can have significant effects on fly physiology and fitness (2,70,76), the host could be under selection to maintain only the most beneficial symbionts for that particular diet or location.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, since bacteria and fungi are recognized and cleared by semi-independent innate immunity pathways (42), a more nuanced control of the two symbiont groups is also possible. As both bacteria and yeasts can have significant effects on fly physiology and fitness (2,70,76), the host could be under selection to maintain only the most beneficial symbionts for that particular diet or location.…”
Section: Discussionmentioning
confidence: 99%
“…Only the 2,466 reads that were assigned with 100% confidence to the phylum Ascomycota were included in the final analysis. We chose to focus on the Ascomycota because previous studies had identified members of the phylum as important to Drosophila survival and fitness (2,4). The non-Ascomycota reads included 424 from the phylum Basidiomycota (see Data Set S4 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the main model system in which yeasts have come to be understood as food sources is that of fruit flies, a system that might be highly derived. For D. melanogaster, the failure to find and eat yeasts means an early death [39], as these insects use the protein in yeasts for proper immunity and development [99,100].…”
Section: Yeasts As Food Sourcesmentioning
confidence: 99%
“…For example, recent work has shown that some Drosophila strains will prefer to lay eggs only on food with yeast on it, whereas others will only lay eggs in substrates where they are absent (Miller et al, 2011). They also prefer oviposition substrates/foods inoculated with certain yeast strains (Vacek et al, 1985;Barker, 1992;Anagnostou et al, 2010), establishing a clear microbial connection to such behaviors in Drosophila. Microbial influences in Drosophila are not limited to yeast (the major protein source for fruit flies).…”
Section: Discussionmentioning
confidence: 99%